Rapid Stopped Flow Assembly Of Multicore Iron Oxide Nanoparticle - Harivindren, Asokan (Universiti Sains Malaysia, 2017)
The rapid stopped-flow assembly of multicore iron oxide nanoparticle (IONP) was performed using the RX2000 Rapid Mixing Unit. IONP was to be stabilized using polymer PSS (Poly(sodium(4)styrenesulfonate)70k with varying concentrations of IONP from 10ppm to 50ppm. With a fixed time of one minute, the adsorption kinetics were obtained. Adsorption kinetic results were unstable and noisy, leading to conclusions that ineffective coating has taken place. Due to the nature of IONP to agglomerate and sedimentate, clusters were formed even before experimental work began, hence leading to kinetics representing the diffusion motion, rather than the adsorption kinetics that is intended. It was concluded that rapid stopped-flow method was not feasible to form multicore iron oxide nanoparticle.